The role of waste banks in realizing good environmental governance in Bandarlampung City - Muhammad Zahid Alim (Journal of Governance and Accountability Studies, 2023)
Purpose: The aim of this research is to analyze the effectiveness of implementing the Waste Bank as an indicator of achieving the principles of Good Environmental Governance in Bandarlampung City in order to increase public awareness regarding the importance of a healthy environment. Research methodology: This study employs a normative method using a descriptive analysis approach. Secondary data were acquired through meticulous literature review and subjected to qualitative analysis. Rigorous literature selection ensured data validity. The outcomes of the analysis served as the basis for accurate conclusions within the research. Results: The research results show that the role of waste banks as an indicator of the principles of good environmental governance in Bandarlampung is not yet effective. Therefore, law enforcement is needed, which covers three aspects: structure, substance, and community culture. Limitations: The population growth in Indonesia, especially in urban areas, is dynamic. This causes a high population, which results in the accumulation of rubbish in people's lives. Contributions: Ineffective waste management is the basic reason for the Bandarlampung City Government to collaborate with Bandarlampung City Cleaning Service to socialize the role of waste banks. This socialization activity is an effort to enable people to carry out 3M activities (Draining, Covering and Burying) and use waste as a business opportunity.